Neither dichotomous nor split, but schema-related negative interpersonal evaluations characterize borderline patients - Sieswerda, Simkje; Barnow, Sven; Verheul, Roel; Arntz, Arnoud (Journal of personality disorders, 2013)
Cognitive models explain extreme thoughts, affects, and behaviors of patients with Borderline Personality Disorder (BPD) by specific mal-adaptive schemas and dichotomous thinking. Psychodynamic theories ascribe these to splitting. This study expanded the study of Veen and Arntz (2000) and investigated whether extreme evaluations in BPD are (1) dichotomous, negativistic, or split; (2) limited to specific (schema-related) interpersonal situations; and (3) related to traumatic childhood experiences. BPD (n = 18), cluster C personality disorder (n = 16), and nonpatient (n = 17) groups were asked to judge 16 characters portrayed in film fragments in a specific or nonspecific context and with negative, positive, or neutral roles on visual analogue scales. These scales were divided in negative-positive trait opposites related to BPD schemas, negative-positive trait opposites unrelated to BPD schemas, and neutral trait opposites. Interpersonal evaluations of patients with BPD were (1) negativistic; (2) schema related; and (3) partially related to traumatic childhood experiences. Negative evaluations of caring characters in an intimate context particularly characterized BPD. No evidence was found for dichotomous thinking or splitting in BPD.
Published online: January 2013
Gesehen am 27.01.2022